The Effect of Entrepreneurship and Innovation on the Academic Performance of Universities - Tekin, Erol (Turkish Academy of Sciences, 2021)
The aim of the study is to examine the effect of entrepreneurship and innovation on universities' academic performance. For this purpose, we used panel data obtained from the universities included on the Entrepreneurial and Innovative University Index for the 2012-2017 period. The data were obtained from the TÜBİTAK index and URAP. The data obtained were analyzed using the panel regression method. The results show that entrepreneurial and innovative universities have higher academic success. Also, scientific and technological research competence, cooperation and interaction, and economic contribution and commercialization have a significant positive effect on universities' performance. However, the intellectual property dimension of entrepreneurship and innovation significantly and negatively affect universities' academic performance. The entrepreneurship and innovation culture dimension, on the other hand, has no significant effect on universities' performance. The study aims to contribute to the academic literature as a pioneering study that addresses the effect of entrepreneurship on the academic performance of universities. In addition, it is an important study since it shows that universities should add entrepreneurship to their educational and researcher identities while making their choices in positioning themselves among others.
Keywords: 9. Industry and infrastructure; 4. Education; 11. Sustainability; 8. Economic growth; 1. No poverty; 12. Responsible consumption